2018
DOI: 10.14233/ajchem.2019.21455
|View full text |Cite
|
Sign up to set email alerts
|

Development of 5-(Aryl)-3-phenyl-1H-pyrazole Derivatives as Potent Antimicrobial Compounds

Abstract: INTRODUCTIONChalcones (1) and pyrazoles (2) are the most important classes of flavonoids and alkaloids respectively present across the whole plant kingdom [1,2]. Both have interesting bioactive features associated with several biological activities. Chalcones and their derivatives demonstrate wide range of biological activities such as antidiabetic, antineoplastic, antihypertensive, antiretroviral, anti-inflammatory [3], antiparasitic [4], antihistaminic [5], antimalarial [6], antioxidant [7], antifungal [8], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…They demonstrated that pyrazole (1,2-diazole) can be used to Pyrazole derivatives act on diverse and relevant biological targets, which make them attractive for the development of PET tracers, and possess a wide range of pharmaceutical activities. Abdel-Maksoud et al have demonstrated antitumoral activity of several compounds with a pyrazole and sulfonamide moieties [19]; antibacterial and antifungal activity of pyrazole was demonstrated by Chowdary et al [20]. Pyrazoles also showed good activity as monoamine oxidase inhibitors, antidepressant and anticonvulsant agents [21], as BRAF inhibitors [22] and DNA gyrase inhibitors [23] and present antileishmanial, anti-inflammatory, analgesic, antidiabetic and cannabinoid activity; cyclin-dependent kinase and tissue-nonspecific alkaline phosphatase inhibitory activity and moderate antihepatotoxic activity, among others [9,11,[24][25][26][27][28][29].…”
Section: Pyrazolesmentioning
confidence: 99%
“…They demonstrated that pyrazole (1,2-diazole) can be used to Pyrazole derivatives act on diverse and relevant biological targets, which make them attractive for the development of PET tracers, and possess a wide range of pharmaceutical activities. Abdel-Maksoud et al have demonstrated antitumoral activity of several compounds with a pyrazole and sulfonamide moieties [19]; antibacterial and antifungal activity of pyrazole was demonstrated by Chowdary et al [20]. Pyrazoles also showed good activity as monoamine oxidase inhibitors, antidepressant and anticonvulsant agents [21], as BRAF inhibitors [22] and DNA gyrase inhibitors [23] and present antileishmanial, anti-inflammatory, analgesic, antidiabetic and cannabinoid activity; cyclin-dependent kinase and tissue-nonspecific alkaline phosphatase inhibitory activity and moderate antihepatotoxic activity, among others [9,11,[24][25][26][27][28][29].…”
Section: Pyrazolesmentioning
confidence: 99%
“…Pyrazoles have attracted increased attention in recent years owing to their widespread applications in medicine [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], agriculture, [ 16 ] materials science [ 17 , 18 , 19 , 20 ], and catalysis [ 21 , 22 ]. In this review, the chemistry of a particular kind of pyrazoles, the vinylpyrazoles, is revisited.…”
Section: Introductionmentioning
confidence: 99%
“…Three partially reduced forms may also exist: 1-pyrazolines 2, 2-pyrazolines 3 and 3-pyrazolines 4, and a fully reduced form known as pyrazolidine 5 (Figure 1) [1,2]. Pyrazole and its derivatives occupy a prime place in medicinal chemistry because they are present in several drugs with real medicinal applications, such as celecoxib (Celebrex ® ), sildenafil (Viagra ® ), rimonabant, lonazolac, fomepizole, penthiopyrad, doramapimod, sulfaphenazole and in several remarkable compounds with a wide range of pharmacological activities, namely anticancer [3], analgesic, anti-inflammatory and antioxidant [4][5][6][7], antibacterial and antifungal [8,9] antipyretic, antidepressant and anticonvulsant [10,11], antidiabetic [12] and cannabinoid activities [13,14], among Pyrazole and its derivatives occupy a prime place in medicinal chemistry because they are present in several drugs with real medicinal applications, such as celecoxib (Celebrex ® ), sildenafil (Viagra ® ), rimonabant, lonazolac, fomepizole, penthiopyrad, doramapimod, sulfaphenazole and in several remarkable compounds with a wide range of pharmacological activities, namely anticancer [3], analgesic, anti-inflammatory and antioxidant [4][5][6][7], antibacterial and antifungal [8,9] antipyretic, antidepressant and anticonvulsant [10,11], antidiabetic [12] and cannabinoid activities [13,14], among others [15][16][17][18][19][20][21]. Along with the medicinal applications, pyrazoles are also useful as agrochemicals, such as herbicides, others [15]…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole and its derivatives occupy a prime place in medicinal chemistry because they are present in several drugs with real medicinal applications, such as celecoxib (Celebrex ® ), sildenafil (Viagra ® ), rimonabant, lonazolac, fomepizole, penthiopyrad, doramapimod, sulfaphenazole and in several remarkable compounds with a wide range of pharmacological activities, namely anticancer [ 3 ], analgesic, anti-inflammatory and antioxidant [ 4 , 5 , 6 , 7 ], antibacterial and antifungal [ 8 , 9 ] antipyretic, antidepressant and anticonvulsant [ 10 , 11 ], antidiabetic [ 12 ] and cannabinoid activities [ 13 , 14 ], among others [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Along with the medicinal applications, pyrazoles are also useful as agrochemicals, such as herbicides, fungicides, and insecticides [ 22 ] and possess other applications, such as dyestuffs, sunscreen materials [ 23 , 24 ], analytical reagents and pluripotent ligands in coordination chemistry [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%